Esophageal Cancer: Surgical Strategies - Costa, Paulo (2014)
Introduction: Oesophagectomy for cancer is associated to a significant morbidity and mortality. The superiority of transthoracic vs transhiatal is still a matter of controversy. The aim of this paper is to discuss the results of a series of patients submitted to either a transthoracic or a transhiatal according to the anatomic location regarding the carina.Material and Methods: Retrospective analysis of 52 consecutive patients, with oesophageal carcinoma, 7 female and 45 males, median age 64 [46-85] years. Location: cervical – 1; above carina - 22; below or at carina level - 19; cardia type I –10. 19 adenocarcinoma, 32 squamous cells, 1 lymphoma. Twenty patients (40%) – neo-adjuvant therapy. Thoracoabdominal approach – 3, cervico-thoracoabdominal – 20, transhiatal – 27, exploratory thoracotomy – 2. Gastric pull-up 49 (cervical anastomosis – 46; thoracic - 3); cervical oesofagocoloplasty -1.Results: Pathologic staging: complete remission - 8; Ib – 3; IIa – 9; IIb - 4; IIa – 11; IIIb -2; IIIc – 10; IV – 1; non-stageable - 3. Major complications: 37%. Resectability: 96% (50/52). Mortality: 4th week - 6%; in-hospital - 14%. Median survival 18 months [3-80]. Survival Curves (Kaplan-Meier): 2 years - 47%; 5 years - 19% (transthoracic vs transhiatal p > 0.05).Discussion: Selection of surgical approach based on the anatomic location of the tumour regarding the carina was safe, the resectability was high and similar when a transthoracic or a transhiatal was planed and carry-on.Conclusions: In this series of oesophageal cancer patients, in advanced pathologic condition (52% p Stages III/IV) the overall survival was similar for transthoracic and transhiatal. Neo-adjuvant treatments definitively contributed to enhance resectability.Keywords: Esophagectomy; Laparoscopy; Esophageal Neoplasms/surgery; Thoracotomy.